2022
DOI: 10.2147/jir.s359498
|View full text |Cite
|
Sign up to set email alerts
|

Combining Pre- and Postoperative Lymphocyte–C-Reactive Protein Ratios Can Better Predict Hepatocellular Carcinoma Prognosis After Partial Hepatectomy

Abstract: Background Various preoperative inflammatory indicators have been identified as potential predictors of poor prognosis in patients with hepatocellular carcinoma (HCC), but the role of postoperative inflammatory indicators remains unclear. This study aimed to explore the prognostic value of the postoperative lymphocyte–C-reactive protein ratio (PostLCR) on its own and combined with preoperative LCR (PreLCR). Methods A total of 290 patients with primary HCC were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In recent years, the use of a high LCR as a predictor of overall survival has been validated in patients with stomach cancer, hepatocellular carcinoma, bladder cancer, or rectal cancer (19)(20)(21)(22)(23). The results of the present study are consistent with the published literature because high LCR was found to be consistently associated with better overall survival in patients undergoing hemodialysis and in the various subgroups.…”
Section: B Asupporting
confidence: 88%
“…In recent years, the use of a high LCR as a predictor of overall survival has been validated in patients with stomach cancer, hepatocellular carcinoma, bladder cancer, or rectal cancer (19)(20)(21)(22)(23). The results of the present study are consistent with the published literature because high LCR was found to be consistently associated with better overall survival in patients undergoing hemodialysis and in the various subgroups.…”
Section: B Asupporting
confidence: 88%
“…However, 11 were not suitable for inclusion criteria. Finally, we identi ed 31 studies from 29 articles published between 2020 and 2023 [14,15,16,17,18,19,20,21,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. The ow diagram of the literature search was shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…In this study, for the first time, we found that LCR could be used as an independent prognostic marker in breast cancer patients. Previous studies reported that LCR is associated with poor prognosis in other tumors, such as colorectal cancer 33 , gastric cancer 32 , and hepatocellular carcinoma 44 . As for IR prognostic indicators, previous studies have shown that LHR is associated with poor prognosis in colorectal cancer 45,46 and gastric cancer 47 .…”
Section: Discussionmentioning
confidence: 98%